If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(9 + x) = 48 (9 * 4 + x * 4) = 48 (36 + 4x) = 48 Solving 36 + 4x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 4x = 48 + -36 Combine like terms: 36 + -36 = 0 0 + 4x = 48 + -36 4x = 48 + -36 Combine like terms: 48 + -36 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 4(9+x)=4 | | 0.5(m-10)=21 | | 3x+6=8x+16 | | 23.00=4g+3.68 | | 0.2w=0.02 | | 48=3(x+2)(x-4) | | 34-(x+8)=9x-4 | | -4m-24=-4(1+6m) | | 25-v-14=9 | | 19=x-5+x | | 3x=68-x | | 16x^3+32x^6+27x^4= | | 6.5=8.9-0.4x | | 0=2z-4 | | 12.44=2g+3.82 | | 6x+2(2x-1)=10 | | .5x+.45(50)=39.5 | | 10.5x=100000 | | 5(6x-6)=60 | | 0.8y+25=-1 | | 6+8q=9+7q | | -7(2x+6)=42 | | (x-10)(x-5)=(x+9)(x+9) | | -6+2x=-6x+34 | | 3x-6=-26-7x | | 12x=4x | | 5n+6n=-99 | | -(x+3)-1=4x+7(x+8) | | 4(x+8)=4(3x+12) | | 17+h-3=-9 | | 3x+2-x=-22 | | 5x+25=13x-7 |